Analisis Proses dan Hasil Audit Penghitungan Kerugian Keuangan Negara Kasus Korupsi Importasi Gula pada Kementerian Perdagangan Tahun 2015-2016 - Hamdani, Hamdani; Oktafiani, Salsabilla (Universitas Batanghari Jambi, 2026)
This study aims to analyze the process and results of the state financial loss audit (PKKN) in the case of alleged corruption in sugar imports at the Ministry of Trade in 2015-2016. This study uses a qualitative approach. The research data was obtained from secondary data in the form of audit reports from the Supreme Audit Agency (BPK) and the Financial and Development Supervisory Agency (BPKP), indictments, and relevant court decisions. Data analysis was conducted using inductive and deductive techniques. The results of the study indicate that the PKKN audit by BPKP in the case of alleged corruption in sugar imports did not fully meet investigative audit standards in terms of inter-agency coordination, independence, objectivity, and professional accuracy. The determination of the amount of state financial losses also did not meet the criteria of actual and definite losses and was not supported by a strong methodological and juridical basis.